Coupling of electrodialysis and leaching processes for removing of cadmium from phosphate ore. Issue 4 (3rd March 2016) - Benredjem, Zahia; Delimi, Rachid; Khelalfa, Assia; Saaidia, Samia; Mehellou, Ahmed
ABSTRACT: Phosphate rock is a valuable material that is used for the production of large phosphorus chemicals. However, this natural material usually contains some toxic elements such as cadmium (Cd). Cd is a non-nutritive metal regarded as harmful to both humans and the environment. The main toxic effects of Cd on human health are the kidney and renal cortex diseases. Other effects were observed on pulmonary, cardiovascular, and musculoskeletal systems, in addition to including Cd as a human carcinogen. In order to reduce the cadmium content in the phosphate ore, an original method was studied and consists of coupling both leaching and electrodialysis. The effects of process parameters, such as reaction time, nature, and concentration of the extracting agent, liquid/phosphate ore ratio, pH, temperature, and current density, were investigated. The obtained results show that the cadmium extraction from phosphate ore using simple batch leaching does not reduce the cadmium content to the required level. However, the application of leaching- electrodialysis coupled method at optimum current density of 10 mA cm −2 increases the cadmium extraction efficiency up to 84.3%. This synergetic process could be applied to the treatment of phosphate ore containing cadmium.